Acknowledgment to Reviewers of European Journal of Investigation in Health, Psychology and Education in 2020 - EJIHPE Editorial Office (MDPI AG, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that European Journal of Investigation in Health, Psychology and Education maintains its standards for the high quality of its published papers [...]